Design of TSSFD technique and its application study in a traditional pump manufacturing company. (25th May 2022) - Thirunavukkarasu, V.; Devadasan, S.R.
During the last two decades Six Sigma concept and Quality Function Deployment (QFD) technique have been widely applied in various types of organisation. The common goal of Six Sigma and QFD is achieving customer satisfaction. Yet QFD is rarely found in Six Sigma programs. Hence, the research community has just started to indicate the importance of impregnating QFD in Six Sigma programme. In this context, during the research reported in this paper the technique called Total Quality Function Deployment (TQFD) was impregnated with Six Sigma concept to evolve a model named as Total Six Sigma Function Deployment (TSSFD). The application of TSSFD was studied by examining it in a pump-manufacturing environment. The anticipated results of this application study were fruitful and helped in unearthing hidden facts that are currently obstructing the pump industry to achieve Six Sigma level quality through the translation of customer voices into practically understandable languages.